PENGARUH PARADIGMA LINGKUNGAN DAN PERSONAL VALUE TERHADAP CARBON FOOTPRINT MAHASISWA - Ali Sibro Malisi; Nadiroh Nadiroh (Program Studi Manajemen Lingkungan, 2017)
The objective of the research was aimed to finding the influence of environmental paradigm and personal value on environmental issues. Here, the effect of environmental paradigm and personal value on environmental using Carbon Footprint Analysis were evaluated on students at Universitas Negeri Jakarta. This research uses quantitative expost facto method with sample of 194 students. The results showed that there is influence of environmental paradigm and personal value to total carbon footprint of student. It is known that the student's carbon footprint which has DSP paradigm is bigger than the student with NEP paradigm. This also applies to personal values, it is known that students who have egoistic personal values have a greater carbon footprint than those with personal value altruistic and biospheric. Based on the results of this study, it can be concluded carbon footprint is affected by environmental paradigm and personal value.